Three new cryptic species of the freshwater zooplankton genus Holopedium (Crustacea: Branchiopoda: Ctenopoda), revealed by genetic methods - Rowe, Chad L.; Adamowicz, Sarah J.; Hebert, Paul D. (Zootaxa, 2007)
Molecular approaches have greatly advanced our understanding of species diversity and biogeography in the cladoceran crustaceans. Here, we provide the first large-scale examination of taxonomic diversity in the genus Holopedium Zaddach, 1855, by characterizing patterns of allozyme, mtDNA, and morphological variation from a total of 193 sites from three continents, including collections from near the type localities for the two generally recognized species, Holopedium gibberum Zaddach, 1855, and Holopedium amazonicum Stingelin, 1904. Allozyme data were only available for North American samples but revealed the presence of four species. Divergence patterns in the mitochondrial cytochrome c oxidase subunit I (COI) gene supported those species, as well as a fifth taxon endemic to South America. The five putative species are separated by substantial sequence (8.7–24.5%) and allozyme (0.36–1.54 Nei’s distance) divergences, while intraspecific genetic diversity was generally limited in comparison. Although two of these species exhibited little morphological differentiation from their closest relatives, and diagnostic traits were not found among the characters considered, a population-level approach revealed significant morphological differences among all pairs of taxa. We therefore present both an allozyme key and a morphological/geographic key to all species, as well as new or augmented descriptions for all five species. H. gibberum s.s. is distributed in Europe and across arctic North America, while its cryptic sister species, H. glacialis n. sp., is widely distributed across temperate North America. H. amazonicum s.s. is apparently restricted to the Amazon basin, H. atlanticum n. sp. occurs in lakes along the eastern margin of North America, while H. acidophilum n. sp. occurs sporadically across North America along a narrow band of middle latitudes. Due to high morphological variability within species, as well as the detection of cryptic diversity, we suggest that genetic analyses should be performed on populations from other geographic regions and should always accompany the recognition of new species of Holopedium.